Antibiotic use for respiratory tract infections in nursing homes: a multicentre cross-sectional study - Llor, Carl; Morros, Rosa; Mateos-Nozal, Jesús; Zárate Sáez, Carlota Manuela; Vaquero Pinto, María N.; Rodríguez Jiménez, Consuelo; Sáez Bejar, Carmen; Magallón-Botaya, Rosa; Matovelle, Priscila; Navarro Sanmartín, Alicia; López Pérez, Elena; García-Sangenís, Ana; et al. (Frontiers in Pharmacology, 2026)
IntroductionTo evaluate the use of antibiotic treatment for respiratory tract infections (RTIs) in nursing homes in Spain, assess whether they were indicated based on current guidelines, and identify predictors of both use and inappropriate use of antibiotics.MethodsCross-sectional study carried out in 34 nursing homes in five areas in Spain. Nursing staff self-registered residents related to antibiotic use for RTIs in February-April 2023. Nursing staff recorded data on residents with RTIs, including demographics, symptoms, diagnoses, and antibiotic use. Logistic regression models were applied to identify predictors of antibiotic prescription and inappropriate use based on clinical guidelines.ResultsAmong 533 recorded RTI cases, the most common diagnoses were common cold (19.7%) and acute bronchitis (18.8%). Antibiotics were prescribed in 77.5% of cases, mainly for otitis media, tonsillitis, and pneumonia, with amoxicillin-clavulanate being the most frequent (34%). Of 328 prescriptions assessed, 63.1% were deemed unnecessary. Factors strongly associated with antibiotic use included confusion (odds ratio 4.72; p = 0.005), perceived demand for antibiotics (OR 3.83; p < 0.001), and fever (OR 3.27; p = 0.005), whereas rhinorrhea reduced the likelihood of prescription (OR 0.23; p < 0.001).DiscussionThe findings reveal substantial overuse of antibiotics for RTIs in nursing homes and highlight the need for targeted interventions to promote guideline-based prescribing and reduce inappropriate use.